1984
DOI: 10.1099/0022-1317-65-6-1043
|View full text |Cite
|
Sign up to set email alerts
|

Production of Virions with Retrovirus Morphology by Human Embryonal Carcinoma Cells in vitro

Abstract: SUMMARYEmbryonal carcinoma (EC) cell lines established from human testicular germ-cell tumours produce, at low frequency, virions morphologically identical to type C retroviruses that have been observed by other workers in human placental tissues. The virus particles are formed while budding from the cell surface, and their numbers are increased by inducing the EC ceils with 5-iodo-2'-deoxyuridine and dexamethasone. Assays for RNA-dependent DNA polymerase (reverse transcriptase) associated with purified virion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Although low levels of mutation and retrotransposition in the germline are required to generate the genetic variation essential for evolution, high levels of mutation or retrotransposition are deleterious to the survival of a species. In humans, endogenous retroviruses with intact coding sequences comprise a very small proportion of the genome [48], yet intact endogenous retroviral particles are found in human pluripotent stem cells, and in testicular germ cell tumours where the expression of endogenous retroviral proteins has been suggested to contribute to tumourigenesis [39],[43],[49]. Furthermore, a number of human genetic diseases are associated with de novo mutagenic retrotransposition events that disrupt the function of endogenous human genes [50],[51].…”
Section: Discussionmentioning
confidence: 99%
“…Although low levels of mutation and retrotransposition in the germline are required to generate the genetic variation essential for evolution, high levels of mutation or retrotransposition are deleterious to the survival of a species. In humans, endogenous retroviruses with intact coding sequences comprise a very small proportion of the genome [48], yet intact endogenous retroviral particles are found in human pluripotent stem cells, and in testicular germ cell tumours where the expression of endogenous retroviral proteins has been suggested to contribute to tumourigenesis [39],[43],[49]. Furthermore, a number of human genetic diseases are associated with de novo mutagenic retrotransposition events that disrupt the function of endogenous human genes [50],[51].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to determine whether type C viral particles occurred in male reproductive tissues were carried out. Bronson et al (20,21) and Kurth et al (97) found that testicular teratocarcinoma cell lines infrequently produced type C virus particles unless exposed first to an inducing agent such as 5-iodo-2Јdeoxyuridine, dexamethasone, or dimethyl sulfoxide. Cell lines differed in responsiveness.…”
Section: Electron Microscopy Studiesmentioning
confidence: 99%
“…Analysis of the available RTVL-Hp sequence data indicates that a similar approach may be successful with RTVL-Hp elements. In addition, in light of the observed transcripts of RTVL-Hp elements in Tera-1 cells, it will be of interest to investigate the possible association between RTVL-Hp elements and the retrovirus-like particles de-tected in that and other teratocarcinoma cell lines (2,23,27). It is also interesting that RTVL-Hp-specific RNAs of 8.0 and 8.6 kb, the approximate size of a prototypical retroviral genomic RNA, are expressed in Tera-1 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%